(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Information may be found at libraries. When most people think "library," they think of books. While it is true, books now come in a variety of forms, including e-books and audio books. Libraries are more than just repositories of books; they give people free access to a plethora of information that is typically unavailable elsewhere, whether online, in print, or in person. Libraries serve a fundamental role in society as portals to knowledge and culture. They offer resources and services that create learning opportunities, encourage achievement and education, and promote the fresh perspectives and ideas essential to a unique and dynamic society. They also make it easier to confirm that data recordings generated and gathered by earlier generations are legitimate. It could be difficult to progress human knowledge and analysis, or to safeguard the world’s rich cultural heritage for future generations, in a world without libraries. Explore briefly in this essay what function libraries will serve in our contemporary society going forward.